Unveiling the dark side of eating disorders: evidence on the role of dark triad and body uneasiness in youth - Giancola, Marco; D’Amico, Simonetta; Vinciguerra, Maria Giulia (Frontiers in Psychology, 2024)
Eating disorders comprise an array of mental disturbance with profound implications for individuals' psychophysical and societal well-being. Extensive research has elucidated the role of the Big Five personality traits in explaining individual differences in the risk of eating disorders, overshadowing alternative personality taxonomies, such as the Dark Triad -DT (i.e., Machiavellianism, psychopathy, and narcissism). Accordingly, the current study aimed to address the association between DT and the risk of eating disorders, also exploring the potential involvement of body uneasiness as captured in terms of weight phobia (fear of being or becoming fat), body image concerns (worries related to physical appearance), avoidance (body image related avoidance behaviours), compulsive selfmonitoring (compulsive checking of physical appearance), and depersonalisation (detachment and estrangement feelings towards one's own body). By using an online cross-sectional design, data were gathered from 419 participants. Results indicated that among the three dimensions of DT, only narcissism exhibited a positive correlation with the risk of eating disorders, while only weight phobia mediated this association. These findings yield theoretical implications extending the knowledge about the role of DT and body uneasiness in the risk of eating disorders. These results also have implications for tailoring prevention or treatment strategies to reduce the risk of eating disorders. Limitations and avenues for future research directions are discussed.